BREAD SALES ADMINISTRATIVE APPLICATIONS IN STORES "ALOHA" BY USING FOXBASE - Joki Wamusanjaz; Irfan, SKom, MM Irfan, SKom, MM (Jurnal Sistem Informasi, 2002)
In scientific writing, entitled Application of Sales Administration at Bread Bakery "Aloha" by using Foxbase, especially on the part of the administrative management which is important because the technology is precise and accurate information is required in many fields and companies towards developing better to improve the quality of . Aloha bakery was founded in 1986 by Mr. Haji Sudijadi, a shop that makes and sells reoti wet bread like brown bread, cheese and other fresh and dried foods such as dry toast HSDPA and other kinds of bread. The purpose of this paper was originally due to be based on impulse and desire bakery is on the administrative management of the bread sales.